The role of the probiotic Akkermansia muciniphila in brain functions: insights underpinning therapeutic potential. (4th March 2023) - Xu, Ruiling; Zhang, Yuxuan; Chen, Shurui; Zeng, Yaohui; Fu, Xuan; Chen, Ti; Luo, Shilin; Zhang, Xiaojie
Abstract: The role of Akkermansia muciniphila, one of the most abundant microorganisms of the intestinal microbiota, has been studied extensively in metabolic diseases, such as obesity and diabetes. It is considered a next-generation probiotic microorganism. Although its mechanism of action has not been fully elucidated, accumulating evidence indicates the important role of A. muciniphila in brain functions via the gut-brain axis and its potential as a therapeutic target in various neuropsychiatric disorders. However, only a limited number of studies, particularly clinical studies, have directly assessed the therapeutic effects of A. muciniphila interventions in these disorders. This is the first review to discuss the comprehensive mechanism of A. muciniphila in the gut-brain axis via the protection of the intestinal mucosal barrier and modulation of the immune system and metabolites, such as short-chain fatty acids, amino acids, and amino acid derivatives. Additionally, the role of A. muciniphila and its therapeutic potential in various neuropsychiatric disorders, including Alzheimer's disease and cognitive deficit, amyotrophic lateral sclerosis, Parkinson's disease, and multiple sclerosis, have been discussed. The review suggests the potential role of A. muciniphila in healthy brain functions.